"An Economics of Capital": Genealogies of Everyday Financial Conduct. Issue 2 (12th February 2017) - Aitken, Rob
Abstract: Although recent forms of neoliberalism have been associated with everyday forms of 'investment', this paper argues that the financial conduct of everyday populations has long been an intense site of intervention. Drawing on the history of nineteenth and twentieth‐century Canadian government savings, annuities and tax deferral programs, this paper argues that everyday financial conduct has long been a key site of experimentation and innovation in practices of the self. These programs experiment with a language and practice of investment which emphasizes everyday conduct as a space of individual responsibility attached to diverse political goals. This suggests that enterprise as a mode of self and citizenship has a diverse and longer trajectory that predates neoliberalism. By extension, this paper conclude with a case for more diversified, complicated and historically‐situated analyses of 'neoliberalism'.